A quadratically convergent method for minimizing a sum of euclidean norms with linear constraints - Zhou, Guanglu (American Institute of Mathematical Sciences, 2007)
In this paper we present a globally and quadratically convergent method for the problem of minimizing a sum of Euclidean norms with linear constraints. The quadratic convergence result of this method is obtained without requiring strict complementarity.